MAGNETIC RESONANCE IN THE DIAGNOSIS OF THE MOST COMMON FORMS OF SPINOCEREBELLAR ATAXIA - Tamaš, Olivera (Medicinski podmladak, 2023)
Spinocerebellar ataxias (SCAs) are a heterogeneous group of autosomal dominant ataxias characterized by dominantly progressive evolution of the cerebellar syndrome and other extracerebellar symptoms and signs. Today there are approximately 40 genetic SCAs and this review aims to the describe the clinical picture and magnetic resonance imaging (MRI) findings of the most common SCA subtypes in Europe and Serbia. This is a group of polyglutamine diseases caused by mutations resulting from the expansion of the CAG repeats and accompanied by the loss of neural volume mainly of the cerebellum and the spinal cord. Magnetic resonance has a vital role in the diagnosis because it excludes structural damage as one of the potential causes of ataxia. In addition to this, the loss of volume as demonstrated by MRI serves as a biomarker which helps to monitor the natural progression of different subtypes of the disease. Typical findings in these MRI scans include cortico-cerebellar atrophy, spinal cord atrophy, olivopontocerebellar atrophy and different combinations of the said atrophies. Unfortunately, there are no distinct pathognomonic MRI signs or combinations of signs to facilitate diagnosis. There are, however, similarities in the MRI findings of some of the SCA subtypes, especially at disease onset. The ability to differentiate one pattern of atrophy from another and observing other clinical characteristics can have an important role can be of significant help in the diagnostic process.
Keywords: spinocerebellar ataxia, magnetic resonance imaging, diagnosis